Preventing currency crises in emerging markets - Edwards, Sebastian; Frankel, Jeffrey A.; National Bureau of Economic Research (Chicago : University of Chicago Press, 2002)
Economists and policymakers are still trying to understand the lessons recent financial crises in Asia and other emerging market countries hold for the future of the global financial system. In this timely and important volume, distinguished academics, officials in multilateral organizations, and public and private sector economists explore the causes of and effective policy responses to international currency crises. Topics covered include exchange rate regimes, contagion (transmission of currency crises across countries), the current account of the balance of payments, the role of private sec.
Papers presented at a conference held in Islamorada, Fla., in Jan. 2001.
Includes bibliographical references and indexes.
aia 18/7/16
Loan
Keywords: Currency question; Monetary policy; Financial crises; Developing countries